The Influence of Customer Relationship Management and Satisfaction on Customer Loyalty of the Indonesian Home Education Parenting Program - Zahra, Vatima As; Dewanti, Mentari Clara (Jurnal Ekonomi dan Bisnis Digital, 2024)
Home Education is a bridge between teachers and parents to work together in stimulating growth and development by holding parenting in the city of Surabaya. The purpose of this study was to determine the effect of customer relationship management and satisfaction on customer loyalty in the Home Eduction parenting programme. Using a quantitative approach with a Likert scale using 100 population sampling of kindergarten students in Surabaya. This study uses validity test, reliability test, classical assumption test which includes normality test, multicolinerity test, heteroscedasticity test and linear regression analysis using SPSS software. After testing this research, it can be concluded that Customer Relationship Management and customer satisfaction have a significant positive effect on loyalty and simultaneously affect loyalty by 68%.